2013
DOI: 10.1128/jvi.02023-12
|View full text |Cite
|
Sign up to set email alerts
|

The Adenoviral Oncogene E1A-13S Interacts with a Specific Isoform of the Tumor Suppressor PML To Enhance Viral Transcription

Abstract: PML nuclear bodies (PML NBs), also called ND10, are matrix-bound nuclear structures that have been implicated in a variety of functions, including DNA repair, transcriptional regulation, protein degradation, and tumor suppression. These domains are also known for their potential to mediate an intracellular defense mechanism against many virus types. This is likely why they are targeted and subsequently manipulated by numerous viral proteins. Paradoxically, the genomes of various DNA viruses become associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 104 publications
1
49
1
Order By: Relevance
“…Taken together, these observations support the idea that the E4 Orf3 interaction with PML-II opposes antiviral responses so as to favour productive viral infection, which fits well with the more recent finding that PML-II is needed for a robust type 1 IFN response (Chen et al, 2015). However, it has also been reported that PML-II serves a positive function during Ad5 infection (Berscheminski et al, 2013).…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Taken together, these observations support the idea that the E4 Orf3 interaction with PML-II opposes antiviral responses so as to favour productive viral infection, which fits well with the more recent finding that PML-II is needed for a robust type 1 IFN response (Chen et al, 2015). However, it has also been reported that PML-II serves a positive function during Ad5 infection (Berscheminski et al, 2013).…”
Section: Introductionsupporting
confidence: 76%
“…Previously, Berscheminski and colleagues reported that PML-II was beneficial to Ad5 infection, in apparent contradiction to our findings (Berscheminski et al, 2013). They showed that PML-II potentiated transcriptional activation of a viral early promoter by the E1A 13S protein and that, in a cellular context where all PML proteins were depleted, the addition of exogenous PML-II enhanced virus yield about 3-fold.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It is possible that this interaction plays some role in E1A-mediated transcriptional regulation. An interaction between PML-II and CR3 of E1A was shown to be important for the ability of E1A to activate viral promoters (44), and since DREF is colocalized to PML bodies the two may be linked. Significantly, we observed reduced viral gene expression upon knockdown of DREF (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A central and as-yet unresolved question is whether PML or SP100 plays a role in the early transcription of viral genes after infection (14,42,(47)(48)(49)(50)(51). Both PML and SP100 are degraded within the first 6 hpi, and thus the major effect of PML or SP100 on the transcription of viral DNA would occur during that period (11).…”
Section: At a Low Ratio Of Virus Per Cell δIcp0 Virus Replicates To mentioning
confidence: 99%